2021
DOI: 10.1186/s12890-021-01637-w
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental movement skill proficiency and objectively measured physical activity in children with bronchiectasis: a cross-sectional study

Abstract: Background Bronchiectasis is a major contributor to respiratory morbidity and healthcare utilization in children. Children with bronchiectasis exhibit low levels of physical activity (PA) and poor fundamental movement skills (FMS) may be a contributing factor. However, there are no data on FMS’s in this population. The current study assessed FMS proficiency in children with bronchiectasis and examined associations with objectively measured PA. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In addition to poor exercise tolerance, children repeatedly spoke about their lack of skills or their inability to play games and sports with their peers. This finding is consistent with the results of a recent study examining the relationship between fundamental movement skill proficiency and physical activity in children with bronchiectasis ( 37 ). In that study, fewer than 5% of children demonstrated mastery of locomotor skills such as run, gallop, hop, and leap; while fewer than 10% demonstrated mastery of object control skills such as two-handed strike, overarm throw, and underarm throw.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to poor exercise tolerance, children repeatedly spoke about their lack of skills or their inability to play games and sports with their peers. This finding is consistent with the results of a recent study examining the relationship between fundamental movement skill proficiency and physical activity in children with bronchiectasis ( 37 ). In that study, fewer than 5% of children demonstrated mastery of locomotor skills such as run, gallop, hop, and leap; while fewer than 10% demonstrated mastery of object control skills such as two-handed strike, overarm throw, and underarm throw.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, by improving FMS, the capacity for children with bronchiectasis to engage in sport and other physical activities is potentially enhanced, which may mitigate the risk of disabling secondary conditions such as obesity and depression. In support of this assertion, we had undertaken a cross-sectional study which found that children with bronchiectasis who achieve their age equivalency for FMS have higher levels of physical activity, greater perceived competence, and better health-related QoL ( 10 ). Future trials evaluating the effectiveness of programs to improve FMS in children with chronic respiratory conditions such as bronchiectasis should therefore include a follow-up period of 6–12 months to determine the extent to which improvements in FMS lead to increases in physical activity performance and improvements in health outcomes such as weight status, cardiovascular fitness, and lung function.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study involving 39 children and adolescents with non-CF bronchiectasis reported active video gaming to improve aerobic fitness and muscular strength; however, because exercise was combined with an extensive home-based physiotherapy program comprising ventilatory muscle training and postural drainage with percussion, the independent effects of exercise training on the fitness and respiratory outcomes could not be delineated ( 8 ). We have previously shown that children with bronchiectasis are insufficiently active for health benefit ( 9 ) and exhibit significant developmental delays in fundamental movement skill (FMS) proficiency ( 10 ). Further, children with bronchiectasis who achieve their age equivalency for FMS have higher levels of physical activity ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, inappropriate support and stimulus of motoric could reduce motor coordination [35]. Training activity could be conducted to enhance the mastery of fundamental movement skills [36]. Parents' roles are essential to support the fundamental movement skill [37].…”
Section: Notesmentioning
confidence: 99%